2010
DOI: 10.1007/s11920-009-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Antipsychotic Drugs in Older Adults

Abstract: Antipsychotic medications are widely used to manage psychotic and behavioral disorders in older adults, including primary psychotic disorders such as schizophrenia, and psychosis and behavioral disturbances associated with dementia. These two broad diagnostic indications are associated with contrasting recommended treatment durations, with the former requiring indefinite treatment across the life span. Antipsychotic drug dosing for schizophrenia is based primarily on studies of younger patients and thus may no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 58 publications
1
22
0
2
Order By: Relevance
“…A previous study from India with 53 subjects reported that 53% of the dementia patients were prescribed antipsychotic medications 3 . Findings from this study are similar, but the rate of antipsychotic prescriptions we found is much higher than that in some recent studies from developed countries 16,17 . Over the years, the prescription of atypical antipsychotic prescriptions for dementia patients has declined in developed countries because of elderly patients' increased risk of sudden cardiac death 18 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A previous study from India with 53 subjects reported that 53% of the dementia patients were prescribed antipsychotic medications 3 . Findings from this study are similar, but the rate of antipsychotic prescriptions we found is much higher than that in some recent studies from developed countries 16,17 . Over the years, the prescription of atypical antipsychotic prescriptions for dementia patients has declined in developed countries because of elderly patients' increased risk of sudden cardiac death 18 .…”
Section: Discussionsupporting
confidence: 71%
“…A small proportion of patients in the organic mental disorder group received antidepressants (12.5%). These rates are much lower than the prescription rate of antidepressants reported in developed countries for Alzheimer's patients, which ranges from 32.3% to 40.5% 17 . The reasons for these varying trends must be understood.…”
Section: Discussionmentioning
confidence: 83%
“…Antipsychotics are a class of medications primarily used to manage psychosis (including delusions, hallucinations, or disordered thought), particularly in schizophrenia and bipolar disorders, by alleviating such symptoms as hallucinations, both visual and auditory, and paranoid thoughts [56] . However, the first generation of antipsychotics has usually been associated with elevated cardiovascular mortality due to QTc interval prolongation and may cause TdP.…”
Section: Antipsychotics Toxicity Testingmentioning
confidence: 99%
“…Although mammalian toxicity studies remain the gold standard for risk assessment, the zebrafish has become a valid model due to the toxic responses that appear to be well conserved between mammalians and zebrafish [64] . Cardiotoxicological effects of aripiprazole, clozapine, olanzapine, quetiapine, risperidone and ziprasidone were documented [56] . Aripiprazole, clozapine, olanzapine, quetiapine, risperidone and ziprasidone (first-generation antipsychotics) were assessed using the zebrafish larvae.…”
Section: Antipsychotics Toxicity Testingmentioning
confidence: 99%
“…Il faudrait par contre se méfier d'une réduction automatique, à 60-65 ans, de hautes doses de neuroleptiques prescrits jusque-là, car cela risque de m ener à une exacerbation de la schizophrénie et à une dimiTableau 2 Dosages recommandés chez le schizophrène âgé par Alexopoulos et al [16] et ceux du compendium suisse des médicaments [50]. nution de la qualité de vie [26]. Pour déterminer au mieux la dose minimale des antipsychotiques, les auteurs suggèrent que l'utilisation de données du PET permettraient à terme de développer un modèle de posologie prédictive qui se basera sur les corrélations entre les taux plasmatiques de médi-caments et les liaisons aux récepteurs centraux chez les p atients jeunes et âgés.…”
Section: Posologiesunclassified